Promoting Mental Health And Well-Being In Nursing: A Systematic Review Of Mindfulness Based Interventions (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Nurses in contemporary healthcare face numerous stressors that affect their mental health. Mindfulness-based interventions can help manage these challenges, enhancing their well-being and patient care quality. This research aims to improve the satisfaction and resilience of nursing professionals in demanding healthcare settings.Method: To classify necessary research published between 2018 to 2022, a comprehensive search of databases, including Scopus, PsycINFO and Web of Science, was done. The inclusion criteria for this study were studies written in English that specifically studied to promote the Mental Health and Well-Being among Nursing by Mindfulness Based Interventions, the studies chosen had to use well-established scales for measurement and provide valuable data on team dynamics. Twelve studies were included in the synthesis after initial screening and quality assessment.Results: The synthesis of findings revealed several consistent themes regarding the benefits of MBIs for nurses' mental health. Self-care practices, resilience building, and supportive work environments emerged as critical factors in promoting nurses' well-being. Additionally, education and training were identified as essential components of effective MBI programs, equipping nurses with practical coping skills and enhancing their emotional regulation abilities. The findings also underscored the broader societal implications of promoting nurses' mental health, highlighting the potential impact on staff retention and patient care quality.Conclusion: Study provides valuable insights into the effectiveness of MBIs in promoting mental health and well-being among nursing professionals in Saudi Arabia. By addressing workplace stressors and fostering supportive work environments, MBIs offer promising avenues for enhancing nurses' resilience and improving overall job satisfaction. Moving forward, future research should focus on longitudinal studies to assess the long-term effectiveness of MBIs and explore innovative approaches to integrating mindfulness into nursing practice.Top of Form